Bacterial Profile and Antimicrobial Resistance Patterns of Pleural Empyema in Pekanbaru Hospitals - Yovi, Indra; Safari, Dodi; Syah, Nur Afrainin; Anggraini, Dewi; Hanifah, Zulfa Nur; Shapira, Vanesya Zahrani; Elliyanti, Aisyah (Jurnal Respirologi Indonesia, 2024)
Background: Empyema is a problem worldwide due to its high incidence, mortality, and morbidity rates. So, administering antibiotics is mandatory to treat the disease. It should be sensitive to the causal microorganisms and avoid resistant ones for treatment efficacy. This research aimed to determine bacterial profile and antimicrobial resistance, which can be fundamental foundations for clinical practices in the treatment of patients, especially in Pekanbaru.Methods: This was a cross-sectional study from medical records at Arifin Achmad and Eka Hospitals from January 1, 2015, to December 31, 2022, including culture and antibiotic resistance test results with samples from pleural fluid and antibiotic susceptibility test using VITEK 2.0.Results: A total of 197 pleural fluid specimens were obtained. Gram-negative bacteria were found to be the most prevalent at 79.7%, namely Klebsiella pneumoniae (18.5%), Escherichia coli (12.0%), and Pseudomonas aeruginosa (11.0%). Gram-positive bacteria were found at 12.2%, the most common being Staphylococcus aureus (6.1%) and Enterococcus faecalis (2.0%). Antibiotic sensitivity tests for Gram-negative bacteria showed that amikacin and tigecycline were the most sensitive, and Gram-positive bacteria showed the most sensitivity to linezolid, tigecycline, and vancomycin. The resistance of Klebsiella pneumoniae and Escherichia coli to cephalosporins was 18.5% and 75.0%, respectively. The resistance of Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa to carbapenems was 8.0%, 13.0%, and 53.0%, respectively.Conclusion: Gram-negative is the most common microorganism found in pleural empyema. The resistance of multiresistant bacteria to antibiotics is high and requires supervision to apply appropriate antibiotic administration based on local antimicrobial patterns and the need to strengthen antimicrobial stewardship programs.